Atenção farmacêutica a idosos com síndrome metabólica usuários da estratégia saúde da família - Trindade, Ariane Biolcati [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Metabolic Syndrome is a cluster of risk factors for developing cardiovascular disease and type 2 diabetes. In Brazil, studies have reported that prevalence of the metabolic syndrome varies between 30% and 45% of the population. This scenario demonstrates the need to develop new health care approaches, especially in primary care to prevent, detect and treat complications of metabolic syndrome. The objective of this study was to develop and accomplish a pharmaceutical care model to elderly patients with metabolic syndrome users of the Family Health Strategy (FHS) in order to monitor the biochemical and physiological parameters, and prevent comorbidities. In this prospective clinical study conducted between November 2013 and June 2014, 55 elderly were investigated and divided into two groups. The control group (28) received the traditional care while the intervention group (27), in addition to the traditional care, had pharmaceutical care. Drug Related Problems (DRPs) were evaluated before and after pharmaceutical care. Adherence to drug therapy, blood pressure, cholesterol, triglycerides, fasting glucose and waist circumference were also evaluated. The meetings with patient took place monthly over six months. In the intervention group, systolic blood pressure was significantly reduced by 13 mmHg and diastolic by 6 mmHg and abdominal circumference decreased from 109,3 cm to 106,9 cm for women and 108,6 cm to 106 cm in men (p <0.05). Total cholesterol did not change significantly in IG, however increased in CG from 183 mg / dL to 211 mg / dL (p <0.05). At the beginning of follow-up, only 10 patients were considered adherent to drug therapy and at the end, 17 adhered to therapy (p<0,05). The most prevalent DRPs were lack of adherence to treatment and need of additional medication. It was detected 68 Drug Related Problems, of which 50 (74%) were ...
Keywords: Metabolic syndrome; Síndrome metabólica; Atenção farmacêutica; Idosos - Assistência farmacêutica; Hipertensão; Família - Saúde e higiene; Saúde pública